Mitochondrial plasticity with exercise training and extreme environments - Boushel, R.; Lundby, C.; Qvortrup, K.; Sahlin, K. (Exercise and Sport Sciences Reviews, 2014)
Mitochondria form a reticulum in skeletal muscle. Exercise training stimulates mitochondrial biogenesis, yet an emerging hypothesis is that training also induces qualitative regulatory changes. Substrate oxidation, oxygen affinity, and biochemical coupling efficiency may be regulated differentially with training and exposure to extreme environments. Threshold training doses inducing mitochondrial upregulation remain to be elucidated considering fitness level.